Breast Pain in an Early Adolescent Male Without Gynecomastia - Agüero, Gonzalo M. (Revista del Hospital Italiano de Buenos Aires, 2026)
Pubertal gynaecomastia is the most common cause of breast symptoms in adolescent boys, such as enlargement, lumps or pain.We report the case of a 13-year-old adolescent with bilateral mastalgia caused by a mechanical/traumatic factor and in the absence of gynecomastia.The diagnostic presumption was based on key points of the anamnesis and physical examination.The anamnesis assessed mechanical and traumatic factors of mastalgia, which are not usually evident at baseline.Physical examination of the nipple-areola complex allows differentiation between gynaecomastia and lipomastia.Ultrasonography is a complementary resource in doubtful cases.
Keywords: adolescent; male; breast pain; gynecomastia; case reports